2022
DOI: 10.1038/s41467-022-28832-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural snapshots of V/A-ATPase reveal the rotary catalytic mechanism of rotary ATPases

Abstract: V/A-ATPase is a motor protein that shares a common rotary catalytic mechanism with FoF1 ATP synthase. When powered by ATP hydrolysis, the V1 domain rotates the central rotor against the A3B3 hexamer, composed of three catalytic AB dimers adopting different conformations (ABopen, ABsemi, and ABclosed). Here, we report the atomic models of 18 catalytic intermediates of the V1 domain of V/A-ATPase under different reaction conditions, determined by single particle cryo-EM. The models reveal that the rotor does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 50 publications
(79 reference statements)
10
42
0
Order By: Relevance
“…Together, these results suggest that 120° rotation does not occur immediately by the zippering motion of ABopen with ATP in the absence of ATP binding on ABsemi. This is consistent with the results of a previous study, in which both the zippering motion of AB open with ATP and hydrolysis of ATP in AB semi drive the unzipper motion of AB closed with the release of ADP and Pi, which are coupled simultaneously with the 120° rotation of the shaft[23].…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Together, these results suggest that 120° rotation does not occur immediately by the zippering motion of ABopen with ATP in the absence of ATP binding on ABsemi. This is consistent with the results of a previous study, in which both the zippering motion of AB open with ATP and hydrolysis of ATP in AB semi drive the unzipper motion of AB closed with the release of ADP and Pi, which are coupled simultaneously with the 120° rotation of the shaft[23].…”
supporting
confidence: 93%
“…Moreover, the structural snapshots indicate three catalytic processes simultaneously proceed; ⅰ) zipper movement in AB open with the ATP, ⅱ) ATP hydrolysis on AB semi , and iii) unzipper movement of AB closed with the release of ADP and Pi. In other words, simultaneous interlocking of the three catalytic processes and 120° rotation of the axis are necessary for continuous catalytic reactions [23]. AB closed should be changed to AB open with a 120° step of the rotor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-molecule studies using fluorescent probes (8)(9)(10)(11), gold nanoparticle (AuNP) or nanorod probes (12)(13)(14)(15)(16)(17)(18)(19)(20), and Förster resonance energy transfer (FRET) (15,21,22) have revealed rotational dynamics of the rotary ATPases for both ATP hydrolysis/synthesis directions. Furthermore, recent cryo-electron microscopic (cryo-EM) single-particle analyses revealed entire architectures of the rotary ATPases with different structural states at atomic resolutions (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). In particular, several studies have demonstrated elastic coupling of FoF1 due to large deformations of the peripheral stalk connecting Fo and F1 (24,28,34).…”
Section: Introductionmentioning
confidence: 99%
“…V/A-ATPases have been subjected to extensive structural analysis by x-ray crystallography, negative stain EM, and cryoEM (Boekema et al, 1999 ; Bernal and Stock, 2004 ; Murata et al, 2005 ; Numoto et al, 2009 ; Lau and Rubinstein, 2010 , 2012 ; Lee et al, 2010 ). Similar to F-type ATP synthase, cryoEM has allowed computational separation of rotational states and elucidation of the a subunit fold by evolutionary covariance analysis (Schep et al, 2016 ), with subsequent high-resolution structures revealing further details of the catalytic mechanism (Zhou and Sazanov, 2019 ; Kishikawa et al, 2022 ).…”
Section: Cryoem Reveals the Diversity Of Atp Synthasesmentioning
confidence: 99%